The Effectiveness of Edu-Entertainment in Improving The Knowledge, Attitude, And Behaviour Brushing Teeth in Students Of Elementary School Sukawati Gianyar Regency - Ni Nyoman Widiari; Desak Putu Yuli Kurniati (Jurusan Keperawatan Gigi Poltekkes kemenkes Denpasar, 2015)
The objetctive of this study is to identify the ffictivenesl of edu-entertainment to improving the knowlwdge, attitude, and behavour brushing teeth in students of elimentary school in Sukswati Gianyar.The study is a quasy esperiment with one school as case group which edu-entertainment methodo and the other school as control group with regular method.The result analyzed with General Linier model shows that there is an improvement of knowledge, attitude, and behavior in brushing teeth of student in 6th grades of elementary school in Sukawat, it is found that the value of p0.005.The average score of knowledge in pre test is 5.04, post test-1 is 6.21, post test-2 is 6.19. The average score of behavior in brushing teeth in pre test iis 5.66, post-1 is6.48 and post test-2 is 6.58. This results shos that there are significant defference from knowledge, attitude, and behaviorur in berushing teeth in students of grade 6th elementary school in Sukawati, Gianyar, with significance value of less than 0.05.The conclusion of this study that the conselliong using edu –entertainment is effective in improving the knowledge, attitude, and behavior in brushing teeth among students at grade VI of elementary schools in Sukawati Gianyar.